Polygenic testing for IVF embryo selection in Singapore: proceed with caution - Chin, Alexis Heng Boon; Lim, Lee Wei; Muhsin, Sayyed Mohamed (BMJ Publishing Group L, 2024)
Singapore, like most affluent East Asian countries, has seen a drastic decline in total fertility rates (TFR) in recent years. In 2022 and 2023, the TFR hit new lows of 1.04 and 0.97 children per woman, respectively. This has dire implications for the country’s future economic growth, as well as national security due to the projected shortfall in conscripted military manpower.